PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Restoran Mie Gacoan Depok) - Alfino Hadi Putranto (2022)
Mie Gacoan is a noodle restaurant which is quite popular in Indonesia. This study aims to analyze the effect of product quality, service quality, and price on purchasing decisions at Mie Gacoan Depok. This study uses a quantitative method using SmartPLS. The population in this study are consumers of Mie Gacoan who are active in Depok City. The number of samples in this study were 100 respondents. Determination of the sample using non-probability sampling technique with purposive sampling type. The data collection technique uses a questionnaire through the Google Form. To analyze and prove this, validity and reliability tests, R-Square tests, Q-Square tests and t-statistic tests are used. Based on the results of the study, (1) product quality has a positive and significant effect on purchasing decisions with a P value of 0.019, (2) service quality has a positive and significant effect on purchasing decisions with a P value of 0.001, and (3) price has a positive and significant effect on purchase decision with a P value of 0.008. Product quality, service quality, and price affect purchasing decisions with an R-Square value of 61.3%, while the remaining 38.7% is influenced by other variables outside of this study such as promotion, brand image, and EWOM.